Mode Choice of Older People Before and After Shopping: A Study with London Data - Su, Fengming; Schmöcker, Jan-Dirk; Bell, Michael G.H. (Journal of Transport and Land Use, 2009)
With the population aging in many countries, older people’s travel is recently getting more attention in the transportation literature. However our understanding of factors influencing their mode choice is still limited. In this research the focus is on mode choice for shopping trips as these are the most frequent trips of older people. The study is not limited to trips to the shopping centre, but investigates the combined mode choice of trips to and from the shop in order to understand also which factors influence mode changes. Two types of models - the multinomial logit (MNL) and the nested logit (NL) - are fitted to data from the London Area Travel Survey. The nesting structure is used to test the correlation in mode choice before and after shopping. A particular focus of the models is on the importance of accessibility variables such as bus and rail stop density and service quality for specific areas of London. The results show that mode choice combinations such as “walk to shop and take the bus back” are not as frequent as sometimes thought and that bus stop density is of more significance to older people than attributes describing the quality of the bus services like service frequency.